Moral Education System : TinyHearts - Yasin, Suhaimi; Muhammad Aiman Hakimi Mahdom,; Muhammad Luqman Haikal Hazni,; Nur Fiqrah Syawanie Mohamad,; Syarifah Haziqah Alhady Syed Mohd Sadik, (Multidisciplinary Applied Research and Innovation, 2025)
Moral Education System : TinyHearts aims to develop a learning system that instructs users on the fundamentals of moral education, emphasizing the importance of good behaviour towards parents, teachers, and peers.  This system provides children with engaging visuals and materials, as well as narration-based assessments that assess their understanding of the significance of good manners towards parents, teachers, and peers. Three categories are provided for users to interact with, featuring informative educational section, educational quizzes and situational quizzes from short animation in the objective of making a system with multi-functional purpose for easier educative system. Each section emphasize its own stronger feature which is delivering information, mindful test and indirect practical test. In summary, this system aims to restore the ethics and decorum of children. This is due to the fact that this system incorporates a learning component, which is supported by an engaging and visually appealing user interface